Participação, mobilização, luta e narrativas orais: a experiência da associação de moradores do bairro Lindéia entre os anos 1970 e 1990 - Fernanda Comparth Pinheiro Oliveira (2021)
This research investigates the history of participation, mobilization and struggle of the residents of the Lindéia neighborhood, in Belo Horizonte, and addresses their oral narratives between the years 1970 and 1990. This period represented the beginning of the residents' articulation in favor of improvements and infrastructure for neighborhood, the culmination of the organization and many achievements with the government and, finally, a period of demobilization that the local residents' association - which was the main mobilization vehicle - lost strength in the neighborhood. The aim of this study is, by looking at Lindéia's micro-history, to discuss the ways that this experience contributes to the understanding of participatory practices and popular mobilization in the city. The narrative is built through the memory of the subject interviewed - in this context specifically related to the experience of the residents' association and moments of political struggle in the Lindéia neighborhood. Based on memories, I present a study of key moments in the neighborhood and the socio-spatial developments triggered by the collective actions of the residents. I try to capture in the words of the local residents what culminated in the initial transformations in the neighborhood and thus, when looking at these everyday accounts, I perceive external connections and interweavings that help in a critical reading of the construction of the urban.